The stigma towards mental illness: Portuguese validation of the Opening Minds Stigma Scale for Healthcare Providers (OMS-HC) - Moreira, Maria Beatriz P.; Pereira, Helena P.; Torres, Inês N.; Marina, Sílvia; Ricou, Miguel (Frontiers in Psychology, 2024)
Background: Stigma towards mental illness significantly contributes to a lower quality of healthcare that can be provided. There are few studies on this topic in Portugal, so validating a scale that can evaluate and study the stigma is paramount. The aim of this study was to validate the Opening Minds Stigma Scale for Portuguese healthcare professionals.Methods: A total of 503 participants were included in this study, and the majority was female (81.1%). The sample consisted mainly of psychologists (39.4%) and physicians (30.8%).Reliability and validity analyses were conducted and included exploratory factor analysis (EFA) and confirmatory factor analysis (CFA).Our results suggest that a 12-item model was the most appropriate (RMSEA = 0.026, SRMR = 0.057, CFI = 0.979, TLI = 0.973, GFI = 0.955) compared to our 15-item model and the original model. Items 8, 9 and 10 were removed. The 12-item scale's internal consistency was adequate (α = 0.71; ω = 0.72).The 12-item model of the scale showed good reliability and validity and is appropriate for use with Portuguese health professionals.